(untitled) (Bangladesh Veterinarian, 2018)
Yield and quality of meats from commercial broiler and indigenous chickens weighing one kg each were studied during different periods of refrigeration. The chicken carcasses were stored at -20oC for 30 days and were analyzed on 0, 15 and 30 days. Carcass weight (%), shank weight (%), dressing (%), breast meat yield (%) were higher (P<0.05) in commercial broilers, but head (%), neck (%), thigh meat (%), drumstick meat (%) were higher (P<0.01) in indigenous chickens. Shank weight (%) decreased with storage time. Higher (P<0.01) percentage of dry matter (DM) and crude protein (CP) were found in indigenous chicken breast meat, while ether extract (EE) and total ash content were higher (P<0.01) in commercial broiler breast meat. Cooking loss (%) was higher in commercial broiler breast meat. The pH and CP (%) decreased, while DM (%), EE (%), Ash (%), Thiobarbituric acid reactive substance (TBARS) value, free fatty acid (FFA) value, and Peroxide value (POV) increased with storage time in both types of chicken. Sensory evaluation showed more juiciness in commercial broiler meat. Bangl. vet. 2017. Vol. 34, No. 2, 61-70